2024
DOI: 10.1007/s12274-024-6576-7
|View full text |Cite
|
Sign up to set email alerts
|

Gate-controlled supercurrent effect in dry-etched Dayem bridges of non-centrosymmetric niobium rhenium

Jennifer Koch,
Carla Cirillo,
Sebastiano Battisti
et al.

Abstract: The application of a gate voltage to control the superconducting current flowing through a nanoscale superconducting constriction, named as gate-controlled supercurrent (GCS), has raised great interest for fundamental and technological reasons. To gain a deeper understanding of this effect and develop superconducting technologies based on it, the material and physical parameters crucial for the GCS effect must be identified. Top-down fabrication protocols should also be optimized to increase device scalability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Most of the samples have been deliberately made with w S much larger than the typical w S (up to ∼200 nm) reported in previous studies on the GCS. 1,[3][4][5][6][7][8][9][10]12,20,22,25,27,28 This has been done to verify the argument that a GCS is easier to observe as w S approaches the coherence length ξ of the S. Our measurement results instead show that GCS can also occur in devices with w S of 550 nm (Figure 1e), which is ∼40 times larger than the ξ of Nb in the diffusive regime (ξ < 15 nm; ref 44). We have not tested devices with larger w S , which may in principle still show GCS.…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…Most of the samples have been deliberately made with w S much larger than the typical w S (up to ∼200 nm) reported in previous studies on the GCS. 1,[3][4][5][6][7][8][9][10]12,20,22,25,27,28 This has been done to verify the argument that a GCS is easier to observe as w S approaches the coherence length ξ of the S. Our measurement results instead show that GCS can also occur in devices with w S of 550 nm (Figure 1e), which is ∼40 times larger than the ξ of Nb in the diffusive regime (ξ < 15 nm; ref 44). We have not tested devices with larger w S , which may in principle still show GCS.…”
Section: Resultsmentioning
confidence: 63%
“…The control of a superconducting current (supercurrent) via the application of a gate voltage ( V G ), currently known as gate-controlled supercurrent (GCS), has become a subject of great interest, as evidenced by the number of experimental and theoretical studies reported on it. Among the main motivations behind the interest in the GCS is its potential for the development of voltage-controlled superconducting logics that would intrinsically have low-energy dissipation (since based on superconductors) and better performance than other superconducting logics already available. Compared to these, GCS-based logics would offer several advantages including higher device density (due to the smaller device size), larger number of devices connectable in series (i.e., higher fan out), stronger resilience to magnetic noise and easier interfacing with conventional metal-oxide semiconductor (CMOS) circuits to form hybrid superconducting/semiconducting computing architectures .…”
mentioning
confidence: 99%
See 3 more Smart Citations